Safety evaluation of early drain removal following pancreaticoduodenectomy: A single-center retrospective cohort study - Xie, Xuehai; Chen, Kai; Liu, Zonghao; Wang, Feng; Ma, Yongsu; Zhang, Shupeng; Shao, Zhijiang; Yang, Yinmo; Tian, Xiaodong (Frontiers in Oncology, 2022)
Objectives: The effects of early drain removal (EDR) on postoperative complications after pancreaticoduodenectomy (PD) remains to be investigated. This single-center retrospective cohort study was designed to explore the safety of EDR after PD. Methods: A total of 112 patients undergoing PD with drain fluid amylase (DFA) on postoperative day (POD) 1 and 3 <= 5000 were divided into EDR and late drain removal (LDR). Propensity Score Matching (PSM) was used. We compared postoperative outcomes between two groups and explore the risk factors of total complications using univariate and multiple logistic regression analyses. Results: No statistical differences were found in primary outcomes, including Grade B/C postoperative pancreatic fistula (POPF) (Original cohort: 5.71% vs. 3.90%; P = 1.000; PSM cohort: 3.33% vs. 6.67%; P = 1.000), and total complications (Original cohort: 17.14% vs. 32.47%; P = 0.093; PSM cohort: 13.33% vs. 33.33%; P = 0.067). The EDR was associated with shorter in-hospital stay (Original cohort: 11 days vs. 15 days; P < 0.0001; PSM cohort: 11 days vs. 15 days; P < 0.0001). Conclusions: EDR on POD 3 is safe for patients undergoing PD with low risk of POPF.